2023
DOI: 10.1080/1478422x.2023.2261782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of refrigerant absorbent combinations in the corrosion resistance of copper as structural material in absorption refrigeration systems (ARS)

Israel Flores-Guadarrama,
José G. Gonzalez-Rodriguez,
Jorge Uruchurtu-Chavarín
et al.

Abstract: The present research was focused on analyzing the corrosion resistance of copper in the presence of refrigerant-absorbent combinations such as lithium bromide (LiBr), lithium nitrate (LiNO 3 ) and calcium chloride (CaCl 2 ), used in Adsorption Refrigeration Systems (ARS). Electrochemical techniques such as open circuit potential, electrochemical impedance spectroscopy, electrochemical noise analyses and potentiodynamic polarisation curves were applied to study the test solution combination effect on the corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In another research work, 316L-type stainless steel was evaluated by When [25] in KCOOH and LiCl-H 2 O, and a lower dissolution rate in KCOOH was found as compared with that in LiCl-H 2 O. In our research, we have evaluated the corrosion behavior of different metals in the CaCl 2 -LiBr-LiNO 3 -H 2 O system instead of LiBr/H 2 O working fluid, finding a significant reduction in the corrosion rates of the different tested alloys [26][27][28]. In some research works [29,30], it has been shown that the LiCl-H 2 O cooling fluids have better thermophysical properties than LiBr-H 2 O.…”
Section: Introductionmentioning
confidence: 91%

Corrosion Behavior of Carbon Steel in LiCl/H2O Mixtures

Avilés-Flores,
Larios-Gálvez,
Martínez-González
et al. 2024
Metals
Self Cite
“…In another research work, 316L-type stainless steel was evaluated by When [25] in KCOOH and LiCl-H 2 O, and a lower dissolution rate in KCOOH was found as compared with that in LiCl-H 2 O. In our research, we have evaluated the corrosion behavior of different metals in the CaCl 2 -LiBr-LiNO 3 -H 2 O system instead of LiBr/H 2 O working fluid, finding a significant reduction in the corrosion rates of the different tested alloys [26][27][28]. In some research works [29,30], it has been shown that the LiCl-H 2 O cooling fluids have better thermophysical properties than LiBr-H 2 O.…”
Section: Introductionmentioning
confidence: 91%

Corrosion Behavior of Carbon Steel in LiCl/H2O Mixtures

Avilés-Flores,
Larios-Gálvez,
Martínez-González
et al. 2024
Metals
Self Cite